Support for the slip hypothesis from whisker-related tactile perception of rats in a noisy environment - Waiblinger, Christian; Brugger, Dominik; Whitmire, Clarissa J.; Stanley, Garrett B.; Schwarz, Cornelius (Frontiers in Integrative Neuroscience, 2015)
Rodents use active whisker movements to explore their environment. The ‘slip hypothesis’ of whisker-related tactile perception entails that short-lived kinematic events (abrupt whisker movements, called ‘slips’, due to bioelastic whisker properties that occur during active touch of textures) carry the decisive texture information. Supporting this hypothesis, previous studies have shown that slip amplitude and frequency occur in a texture dependent way. Further, experiments employing passive pulsatile whisker deflections revealed that perceptual performance based on pulse kinematics (i.e. signatures that resemble slips) is far superior to the one based on time-integrated variables like frequency and intensity. So far, pulsatile stimuli were employed in a noise free environment. However, the realistic scenario involves background noise (e.g. evoked by rubbing across the texture). Therefore, if slips are used for tactile perception, the tactile neuronal system would need to differentiate slip-evoked spikes from those evoked by noise. To test the animals under these more realistic conditions, we presented passive whisker-deflections to head-fixed trained rats, consisting of 'slip-like' events (waveforms mimicking slips occurring with touch of real textures) embedded into background noise. Varying the i) shapes (ramp or pulse), ii) kinematics (amplitude, velocity, etc.), and iii) the probabilities of occurrence of slip-like events, we observed that rats could readily detect slip-like events of different shapes against noisy background. Psychophysical curves revealed that the difference of slip event and noise amplitude determined perception, while increased probability of occurrence (frequency) had barely any effect. These results strongly support the notion that encoding of kinematics dominantly determines whisker-related tactile perception while the computation of frequency or intensity plays a minor role.